2007
DOI: 10.1029/2006gb002788
|View full text |Cite
|
Sign up to set email alerts
|

The interannual variability of oceanic CO2 parameters in the northeast Atlantic subtropical gyre at the ESTOC site

Abstract: [1] The long-term trends and average seasonal variability in the upper ocean inorganic carbon observations were investigated at the ESTOC Station (the European Time Series in the Canary Islands), on the basis of an existing 10-year series (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004). Hydrographic temperature and salinity, together with the pH in total scale at 25°C (pH T ), total alkalinity (A T ), partial pressure of CO 2 expressed as fugacity (fCO 2 ), computed dissolved inorganic carbon (C T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
168
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(199 citation statements)
references
References 59 publications
(101 reference statements)
28
168
3
Order By: Relevance
“…The larger amounts of CO 2 entering into the ocean near Bermuda (Bates, 2007) would be thus advected to the eastern part of the section below the surface. The transport of C ant enriched waters towards the east could explain the existence of higher [C ant ] at this side of the section (tables in appendix A), despite the lower CO 2 uptake rates reported there (Santana-Casiano et al, 2007). It is important to note that there is no complete consensus among the four different methods used to evaluate the storage in C ant for uNACW in the western basin (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The larger amounts of CO 2 entering into the ocean near Bermuda (Bates, 2007) would be thus advected to the eastern part of the section below the surface. The transport of C ant enriched waters towards the east could explain the existence of higher [C ant ] at this side of the section (tables in appendix A), despite the lower CO 2 uptake rates reported there (Santana-Casiano et al, 2007). It is important to note that there is no complete consensus among the four different methods used to evaluate the storage in C ant for uNACW in the western basin (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The equivalent mean DT suggests a slightly higher observed value of 0.93 ± 0.09 µmol·kg -1 ·yr -1 (Fig. 4) 1995 -2004), reported respectively for BATS (Bates, 2007) and ESTOC (Santana-Casiano et al, 2007), indicate that the eastern side of the NASTG has been acting as a much weaker sink for atmospheric CO 2 than the western side. These findings are consistent with previous results, where BATS was found to be in a region of strong spatial gradients in air-sea CO 2 flux (Nelson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to habitat loss, water pollution, eutrophication, and overexploitation, ocean acidification may be another human-induced threat to coastal marine ecosystems and sustainable fisheries. However, little is known about the progress of acidification in coastal oceans at present [Santana-Casiano et al, 2007;Feely et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Sustained observations and modeling studies have shown that oceanic pH is currently decreasing by 0.02 units per decade and is expected to decrease by up to 0.7 units by the year 2100 as a result of atmospheric CO 2 dissolution in the oceans [Bates, 2007;Caldeira and Wickett, 2003;Olafsson et al, 2009;Santana-Casiano et al, 2007]. This ocean acidification (OA) is predicted to affect marine ecosystems through the alteration of community structure [Fabry et al, 2008]; nutrient cycles [Hutchins et al, 2009]; productivity [Riebesell et al, 2007] and carbon export [Mari, 2008;Schulz et al, 2008].…”
Section: Introductionmentioning
confidence: 99%